Resistant personality and burnout in judo athletes from national teams - Ponce Carbajal, Nancy; López Walle, Jeanette M.; Méndez Sánchez, María del Pilar (ECORFAN, 2021)
The objective of this book chapter is to identify the correlations between Hardy Personality (HP) and Burnout (MT), in high performance athletes. The participants were 162 Athletes from their national teams from 21 countries in Judo Sport, who participated in Mundial de Veteranos de Judo and Grand Prix in 2019 in Cancun Quintana Roo, Mexico, the age ranged from 18 to 70 years with an Average of 32.56 and a Standard Deviation of 11.48. The athletes answered two instruments, one that measures the RP that evaluates their resistance to stress, and the other that measures the Burnout. The methodology used is cross-sectional, associative empirical, and simple correlation. Descriptive analyzes, reliability, validity, and Spearman's correlations were performed, with SPSS software. The results found negative and significant relationships in the resistant trifactorial and unifactorial personality. Judokas are perceived as resistant to stress and capable of overcoming any obstacle, there is no depletion or devaluation of their sports practice